The Impact of Teacher Training for Autonomous Learning - Fabela Cárdenas, Martha Armida (Kanda University of International Studies, 2012)
This article focuses on teacher attitudes towards learner autonomy and discusses whether teachers’ attitudes change through teacher training. The study was carried out with teachers working in different self-access centres within the State University of Nuevo Leon, Mexico (UANL). The aim of the study was to report any changes in teachers’ opinions and beliefs on issues after a teacher training course. These issues range from teacher-centeredness, learner-centeredness, learner autonomy, work in the SAC, views on language learning, the role of teachers, the role of learners, views on local culture, and on motivation. The study was carried out using Q Methodology.